Cambridge primary English learner's book 6 - Burt, Sally (United kingdom : Cambridge university press, 2021)
"Cambridge Primary English Learners Book 6" helps young learners improve their English skills through engaging stories, exercises, and activities. It focuses on reading, writing, listening, and speaking, with themes like culture, personal experiences, and the natural world. The book encourages vocabulary building, grammar practice, and creativity, making learning fun and interactive.
Keywords: English : Textbook